Laboratory Monitoring of Direct Oral Anticoagulants (DOACs) - Dunois, Claire (Biomedicines, 2021)
The introduction of direct oral anticoagulants (DOACs), such as dabigatran, rivaroxaban, apixaban, edoxaban, and betrixaban, provides safe and effective alternative to previous anticoagulant therapies. DOACs directly, selectively, and reversibly inhibit factors IIa or Xa. The coagulation effect follows the plasma concentration–time profile of the respective anticoagulant. The short half-life of a DOAC constrains the daily oral intake. Because DOACs have predictable pharmacokinetic and pharmacodynamic responses at a fixed dose, they do not require monitoring. However in specific clinical situations and for particular patient populations, testing may be helpful for patient management. The effect of DOACs on the screening coagulation assays such as prothrombin time (PT), activated partial thromboplastin time (APTT), and thrombin time (TT) is directly linked to reagent composition, and clotting time can be different from reagent to reagent, depending on the DOAC’s reagent sensitivity. Liquid chromatography–mass spectrometry (LC-MS/MS) is considered the gold standard method for DOAC measurement, but it is time consuming and requires expensive equipment. The general consensus for the assessment of a DOAC is clotting or chromogenic assays using specific standard calibrators and controls. This review provides a short summary of DOAC properties and an update on laboratory methods for measuring DOACs.